Advanced thermodynamics : fundamentals, mathematics, applications - Tabatabaian, Mehrzad; Rajput, R. K., 1944- (Mercury Learning & Information, 2018)
Designed for a course in thermodynamics or for use as a reference for practicing engineers, this book includes the theoretical underpinnings and derivations necessary for advanced study. --